ANALISIS DAMPAK EFISIENSI ANGGARAN TERHADAP KINERJA KEUANGAN BADAN PUSAT STATISTIK KOTA MAGELANG - Putri, Sanrina Indriati; Bilqisti, Amarani Robbi (Journal Accounting International Mount Hope, 2025)
Budget efficiency is an important factor in the financial management of government agencies to ensure optimal use of funds. This study aims to analyze the impact of budget efficiency on the financial performance of the Central Statistics Agency (BPS) of Magelang City in 2024 to 2025. With the newly implemented budget efficiency policy, it is important to understand how this policy affects the quality of BPS Magelang City's financial performance. The approach used in this study is descriptive analysis with qualitative methods, data obtained through literature studies and interviews with related parties. The results of the study indicate that budget efficiency has an effect on the optimization of resources and adjustments in the allocation of operational funds. However, if not managed properly, this policy can have an impact on the effectiveness of BPS Magelang City's financial performance.